Construção e estudos psicométricos do Teste Informatizado de Inteligência Emocional para o Trabalho – TIIET - Peixoto, Isaías (Universidade Federal de São Carlos, 2023)
Studies on Emotional Intelligence (EI) are increasingly relevant to scientifically verify the extent to which this variable contributes in various contexts, including the organizational context, which has attributed importance to EI even before scientific studies. However, for such scientific investigations, instruments with psychometric quality are necessary to measure EI specifically in the organizational context. In Brazil, there are currently no psychological tests that evaluate EI specifically for the workplace. Therefore, this research aimed to construct a battery of EI tests for the workplace, the Computerized Test of Emotional Intelligence for Work (TIIET), which aims to be short, with remote/online application, based on the Cognitive Abilities Model of EI and maximum performance. Initially, TIIET consisted of tests that assessed the facets of perception (TPET), understanding (TCET), and emotional management (TGET). The research involved 536 participants and was divided into three studies - articles. The first involved item development, investigation of evidence of content validity, and systematization of TIIET application and scoring. The second sought evidence of validity based on internal structure. Finally, the third article investigated the relationship of TIIET with typical constructs of the workplace to verify evidence of validity based on relationship with other variables. The results of Article 1 indicated favorable content validity indices, with satisfactory item and instruction understanding and adequacy to the proposed theoretical model, as well as indicating that the instrument improved throughout the analyses and improvements suggested by judges, target population, and researchers from the 17 IE research group of the Federal University of São Carlos (UFSCar). In Article 2, the analyses to verify psychometric properties related to CFA, CFA-MG, and precision were consistent with theoretical expectations. Article 3, using Structural Equation Modeling (SEM), presented results that suggest the relationship of EI measured by TIIET with variables of work redesign (proactivity), self-efficacy, well-being, work-family conflict, and family-work. Based on the data obtained through the three articles, positive results are identified that assess evidence of content validity, internal structure, and relationship with other variables for TIIET, specifically for TPET and TGET tests.
The development and psychometric evaluation of the Computerized Emotional Intelligence Test for Work (TIIET)
Keywords: Construção de instrumento; Psicologia organizacional; Validade de conteúdo; Emoção; Regulação emocional; Validade baseada na estrutura interna; Percepção emocional; Gerenciamento emocional; Redesenho no trabalho; Conflito trabalho-família; Bem-estar no trabalho; Instrument construction; Organizational psychology; Content validity; Emotion; Emotional regulation; Internal structure validity; Organizational psychology; Emotional perception; Emotional management; Job crafting; Work-family conflict; Workplace well-being; Validity based on internal structure; CFA; CFA-MG; CIENCIAS HUMANAS::PSICOLOGIA